The Herb Pair Radix Rehmanniae and Cornus Officinalis Attenuated Testicular Damage in Mice With Diabetes Mellitus Through Butyric Acid/Glucagon-Like Peptide-1/Glucagon-Like Peptide-1 Receptor Pathway Mediated by Gut Microbiota - Chen, Yuping; Song, Siyuan; Shu, Anmei; Liu, Liping; Jiang, Jinjin; Jiang, Ming; Wu, Qin; Xu, Huiqin; Sun, Jihu (Frontiers in Microbiology, 2022)
Growing body of research indicates that Traditional Chinese Medicine (TCM) interact with gut microbiota (GM) after oral administration. Radix Rehmanniae and Cornus Officinalis (RR-CO), a well-known TCM pair, is often used to treat diabetes (DM) and its complications. The current study aimed to explore the protective effects of RR-CO on DM induced testicular damage by modulating GM. The RR-CO treatments significantly reduced hyperglycemia, ameliorated testicular ultrastructural damage and inflammation in DM model to varying degrees. Additionally, 16S-ribosomal DNA (rDNA) sequencing results showed that RR-CO treatment increased the amount of butyric acid-producing GM, such as Clostridiaceae_1 family, and decreased the abundance of Catabacter, Marvinbryantia and Helicobacter genera. RR-CO fecal bacteria transplantation (RC-FMT) increased the abundance of Clostridiaceae_1 in the Model FMT (M-FMT) group and ameliorated testicular damage. Furthermore, treatment with RR-CO increased the fecal butyric acid level, serum Glucagon-like peptide-1 (GLP-1) level, and testicular GLP-1 receptor (GLP-1R) expression compared to those in DM mice. Finally, intraperitoneal administration of sodium butyrate (SB) significantly improved the pathological damage to the testis and reduced inflammation in the DM group. These data demonstrated a protective effect of RR-CO on DM-induced testicular damage by modulation of GM, which may be mediated by the butyric acid/GLP/GLP-1R pathway.